Konsep Total Quality Management (TQM) dalam Pendidikan Tinggi - Muhammad Anwar HM (Prodi Manajemen Pendidikan Islam Institut Parahikma Indonesia, 2017)
Total Quality Management, TQM, is something philosophical and comprehensive about live and organization activity which emphasize in continuous improvement as fundamental goal for improving quality, productivity and lessen cost. Implementation of TQM in education still needs long and serious discussion, concerning use of TQM in education is relatively new.